2017
DOI: 10.2147/opth.s141821
|View full text |Cite
|
Sign up to set email alerts
|

Differential association of elevated inflammatory cytokines with postoperative fibrous proliferation and neovascularization after unsuccessful vitrectomy in eyes with proliferative diabetic retinopathy

Abstract: BackgroundPars plana vitrectomy is the only treatment for advanced proliferative diabetic retinopathy (PDR). However, vitrectomy is not always successful despite current progress in vitreoretinal surgical techniques. The aim of our study was to investigate whether the vitreal concentrations of MCP-1, IL-6, IL-8, and VEGF are elevated after unsuccessful vitrectomy in patients with PDR and to investigate whether the altered levels of these cytokines are associated with the cause for the reoperation.Patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Such unspecific upregulation of many cytokines may result from a damage to the retinovascular barrier following retinal detachment. Therefore, the cytokine milieu changes may represent a timely response to the tissue trauma which cannot be attributed to one single biological process [16,33,34,35]. The significant upregulation of pro-fibrotic and pro-inflammatory cytokines in eyes with RD compared to MH found in our study is in good agreement with previous studies that have found similar upregulations compared to eyes with either macular hole, epiretinal membrane or retinal vein occlusion, notably for cytokines as IL-6 and IL-8 [1,16,19,20,36,37], MCP1, MIP-1beta and IP10 [36,38], and in RD with PVR for IL-6, IL-8, IL-10, TNF, INF-gamma, CCL2, CCL3, CCL4, CCL5, CCL11, CCL17, CCL18, CCL19, CXCL9, CXCL19, G-CSF and FGF [2,12,39].…”
Section: Discussionmentioning
confidence: 99%
“…Such unspecific upregulation of many cytokines may result from a damage to the retinovascular barrier following retinal detachment. Therefore, the cytokine milieu changes may represent a timely response to the tissue trauma which cannot be attributed to one single biological process [16,33,34,35]. The significant upregulation of pro-fibrotic and pro-inflammatory cytokines in eyes with RD compared to MH found in our study is in good agreement with previous studies that have found similar upregulations compared to eyes with either macular hole, epiretinal membrane or retinal vein occlusion, notably for cytokines as IL-6 and IL-8 [1,16,19,20,36,37], MCP1, MIP-1beta and IP10 [36,38], and in RD with PVR for IL-6, IL-8, IL-10, TNF, INF-gamma, CCL2, CCL3, CCL4, CCL5, CCL11, CCL17, CCL18, CCL19, CXCL9, CXCL19, G-CSF and FGF [2,12,39].…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular neovascularization is an important clinical manifestation which is the pathological basis for numerous ocular disorders, such as proliferative diabetic retinopathy, ischemic central retinal vein occlusion and retinopathy of prematurity ( 1 – 3 ). No effective treatment for retinal neovascularization (RNV) is available to date.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant finding from the current study was the inflammation. There are several pathways involved in the development of PVR; however, ocular inflammation is the hallmark of PVR formation (Yoshida et al., 2017 ). Inflammation can cause the blood-retina barrier to breakdown.…”
Section: Discussionmentioning
confidence: 99%